Implementation of English Language Teaching Methods under Merdeka Curriculum: A Case Study of Junior High Schools in Palopo - Andi Hasri Tri Ulandari; Rustan Santaria; Wisran Wisran (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study aims to analyze the application of English teaching methods based on the Merdeka Curriculum at the junior high school level in Palopo City. The main focus of this study is to identify the methods used, the barriers faced by teachers, and their perceptions of these methods. This study employs a mixed-methods approach with an explanatory sequential design. Data were collected through observations, questionnaires, and interviews with English teachers at four schools, two public and two private. The results indicate that private schools tend to be more proactive in implementing methods such as project-based learning and communicative language teaching, whereas public schools remain dominated by conventional methods. The barriers faced by teachers are divided into three categories: internal, external, and contextual. However, teachers have a positive perception of the Merdeka Curriculum and demonstrate a willingness to develop more contextual teaching methods. This study recommends the need for ongoing training, improved infrastructure, and policy support to optimize the implementation of the Merdeka Curriculum.